TESTING STUDENTS THROUGH THE WRITING SKILLS - Yuliawati, Fitrah (Universitas Islam Madura, 2016)
Four major skills in communicating through language are often broadly defined as listening, listening and speaking, reading and writing. In many situations where English is taught for general purposes, these skills should be carefully integrated and used to perform as many genuinely communicative tasks as possible. Where this is the case, it is important for the test writer to concentrate on those types of test items which appear directly relevant to the ability to use language for real-life communication, especially in oral interaction. Thus, questions which test the ability to understand and respond appropriately to polite request, advice, instructions, etc. would be preferred to tests of reading aloud or telling stories. In the written section of a test, questions requiring students to write letters, memos, reports and messages would be used in place of many of the more traditional compositions used in the past.